APLIKASI MOBILE-LEARNING UNTUK LONG-LIFE LEARNING - Rokhmah, Betty Eliya (JURNAL RISET MANAJEMEN & AKUNTANSI, 2011)
Long-life learning is a learning process that can be conducted either formally nor informally. The further developments of information and technology will maximize itâs process, one of those developments is mobile learning. Mobile learning will make it easier for its users to conduct anywhere, anytime, throughout their live. This article is intended to give some picture on how mobile learning practice is conducted formally as well as informally.